천연 제올라이트가 충전된 SBBR을 이용한 암모니아성 질소 함유 폐수처리 - 손대희; 정윤철; 유명진 (한국물환경학회, 2003)
Continuous experiments in laboratory scale SBBR (Sequencing batch biofilm reactor) with granular natural zeolites were conducted to investigate the effect of ammonium removal and regeneration by ion-exchange and nitrification. The proposed process used the ion exchange material as the media for the nitrifying and denitrifying biomass. The entire process was carried out in a single reactor. The SBBR type of three reactors were prepared for comparison of removal of nitrogen, organics and phosphorus. The first (modified Zeo-SBBR) and the second (Zeo-SBBR) reactors were filled with granular zeolite, and the third (A.C-SBBR) with granular activated carbon. Modified zeo-SBBR and A.C-SBBR were operated in new mode; fill, mix, drain, backwash, and aeration, and zeo-SBBR in conventional mode; fill, mix, aeration, backwash, and drain. The synthetic wastewater having 200 mg/L of NH4+-N was tested in this process. Results of this experiment were that modified zeo-SBBR showed the highest nitrogen removal efficiency. Total nitrogen removal efficiency showed 94% (modified zeo-SBBR), 75% (zeo-SBBR) and 79% (A.C-SBBR) respectively. In the case of modified zeo-SBBR, nitrogen removal was effectively enhanced by ion-exchange of the zeolite. And the zeolite saturated by ammonium was continuously regenerated by nitrification without a regeneration chemical such as NaCl. The results support that the proposed nitrogen removal process is very effective for treating ammonium bearing wastewater.